The Effects of Aging on Motor Performance - Kleinman, Matthew ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
A review of research on the effects of aging on motor performance provided evidence that age-induced changes within the central nervous system, particularly in the functioning of the non-dominant cortical hemisphere, result in diminished fluid abilities. The loss was most clearly manifested behaviorally as a decreased capacity to perform high-speed, extrinsically-paced motor skills. A study assessed the effects of aging on the performance of intrinsically- and extrinsically-paced motor skills. Seventy-nine subjects (58 females and 21 males) were divided into three groups based on age: 60-65; 65-70; and over 70. Four criterion tasks were assigned: (1) pursuit rotor tracking; (2) mirror tracing; (3) visual choice reaction time; and (4) limb positioning. No significant differences in performance were observed among the three age groups on any of the tasks. There were significant differences between males and females for rotary pursuit tracking at all speeds. There were no significant differences between males and females on the other three tasks. There were no significant interaction effects between age and sex for any of the criterion measures. (JD)
ERIC Note: Document may not reproduce well due to marginal legibility.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Age Differences; Aging (Individuals); Individual Differences; Motor Development; Neurological Organization; Older Adults; Physical Fitness; Psychomotor Skills; Reaction Time; Sex Differences; Reports, Research; Information Analyses